The role of empowering human resources in reducing organizational cynicism - بوخمخم جنات; بوخمخم عبد الفتاح (Finance and Business Economies Review, 2021)
The aim of this study is to determine the nature of the relationship between empowering human resources and the organizational cynicism of employees in University Services Directorate - Jijel - , Through the use of the concept of empowerment, in which this last have an impact on reducing organizational cynicism. The study was based on the data collected by the questionnaire distributed to a sample of 52 permanents employees in University Services Directorate - Jijel - The results showed a high level of empowerment, while the level of organizational cynicism was low, The results of hypothesis testing showed the inverse effect of empowerment on organizational cynicism with its three components (believable, behavioral) While there was no significant relationship between empowerment and emotional cynicism